2021
DOI: 10.4081/aiua.2021.3.280
|View full text |Cite
|
Sign up to set email alerts
|

The presence of chronic inflammation in positive prostate biopsy is associated with upgrading in radical prostatectomy

Abstract: Objective: This study aimed to determine the predictive effect of the presence of chronic prostatitis associated with prostate cancer (PCa) in prostate biopsy on Gleason score upgrade (GSU) in radical prostatectomy (RP) specimens. Materials and methods: The data of 295 patients who underwent open or robotic RP with a diagnosis of localized PCa following biopsy were retrospectively analyzed. Patients were divided into two groups with and without GSU following RP. Predictive factors affecting GSU on biopsy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Given the strong prognostic power of biopsy GG in predicting clinical course and treatment efficacy in almost all stages of PCa, knowledge of preoperative NLR would add information to improve clinical decision making [ 36 ]. Guner E et al reported that the presence or absence of findings of chronic prostatitis on prostate biopsy is associated with the upgrading of surgical specimens [ 37 ]. This also supports the hypothesis that inflammation is associated with prostate cancer upgrading [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the strong prognostic power of biopsy GG in predicting clinical course and treatment efficacy in almost all stages of PCa, knowledge of preoperative NLR would add information to improve clinical decision making [ 36 ]. Guner E et al reported that the presence or absence of findings of chronic prostatitis on prostate biopsy is associated with the upgrading of surgical specimens [ 37 ]. This also supports the hypothesis that inflammation is associated with prostate cancer upgrading [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guner E et al reported that the presence or absence of findings of chronic prostatitis on prostate biopsy is associated with the upgrading of surgical specimens [ 37 ]. This also supports the hypothesis that inflammation is associated with prostate cancer upgrading [ 37 ]. In this study, the direct causal relationship between GG upgrading for RP specimens and the NLR remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Infections such as bacterial prostatitis frequently linked to E. coli or other species of Enterobacteriaceae are identified as the leading causes of prostate inflammation [ 21 ]. In this context, various epidemiological studies have linked prostatitis with prostate cancer risk [ 22 ].…”
Section: Microbiome Inflammation and Prostate Cancermentioning
confidence: 99%
“…The presence of chronic prostatitis was identified to be an independent marker for Gleason score upgrade (GSU) by Guner et al The researchers compared two groups with and without GSU in terms of chronic prostatitis. The study showed that the presence of chronic prostatitis associated with PCa was higher in the patient cohort with GSU in contrast to the other group [ 23 ].…”
Section: The Prostate Microbiome and Chronic Inflammationmentioning
confidence: 99%